2020
DOI: 10.1021/acsami.0c06609
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Enhance the Remodeling of Cell-Free Silk Vascular Scaffolds in Rat Aortae

Abstract: Vascular tissue engineering is aimed at developing regenerative vascular grafts to restore tissue function by bypassing or replacing defective arterial segments with tubular biodegradable scaffolds. Scaffolds are often combined with stem or progenitor cells to prevent acute thrombosis and initiate scaffold remodeling. However, there are limitations to cell-based technologies regarding safety and clinical translation. Extracellular vesicles (EVs) are nanosized particles released by most cell types, including st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
1
35
0
1
Order By: Relevance
“…Loading efficiency can be conveniently calculated by determining the quantity of EVs in the EV isolate solution before and after loading onto the scaffold. Cunnane et al identified a reduction in protein content within the EV isolate after infusing scaffolds with EVs [267]. Results indicated that approximately 45% of the EV isolated protein content was retained within a tubular silk fibroin scaffold.…”
Section: Concentration and Loading Efficiency Of Extracellular Vesicles In Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loading efficiency can be conveniently calculated by determining the quantity of EVs in the EV isolate solution before and after loading onto the scaffold. Cunnane et al identified a reduction in protein content within the EV isolate after infusing scaffolds with EVs [267]. Results indicated that approximately 45% of the EV isolated protein content was retained within a tubular silk fibroin scaffold.…”
Section: Concentration and Loading Efficiency Of Extracellular Vesicles In Biomaterialsmentioning
confidence: 99%
“…More detailed analysis methods are frequently employed by relevant studies, including fluorescent imaging and SEM. In the studies that perform fluorescent imaging of EV-biomaterial systems, the EVs are clearly visible and in most cases a good distribution and near complete coverage of EVs within the biomaterial is achieved [33,215,263,265,267,[270][271][272], although artifacts arising from shedding dye from the EVs labelled with lipophilic dyes cannot be excluded. SEM images of appropriate systems display nanoparticles on the material surface with the morphology typically displayed by EVs [33,267,271,272].…”
Section: Distribution Of Extracellular Vesicles In Biomaterialsmentioning
confidence: 99%
“…The rate of temperature decrease can influence pore size and pore connectivity. By this approach, scaffolds of silk fibroin loaded with extracellular vesicles isolated from Adipose-derived Mesenchymal Stromal Cells (ADMSC) were fabricated ( Cunnane et al, 2020 ). These grafts presented 100% patency at the early stages of the study (4 weeks), compared to the bare scaffold and scaffold seeded with ADMCS prior to implantation.…”
Section: Nanofibrous Scaffold Design For Vascular Tissue Engineeringmentioning
confidence: 99%
“…EVs may represent a more translatable cell-free tool to combine with biodegradable scaffolds intended for vascular grafting applications as we demonstrate here that they are capable of encouraging deposition of ECM structural proteins and therefore likely to encourage positive remodeling of an implanted graft. Indeed, our group has already shown that incorporating EVs into vascular grafts results in increased elastin and collagen production compared to blank scaffolds [ 33 ]. The matrix synthesizing effects exhibited by EVs in this study are therefore readily transferable to the production of de novo vascular graft tissue in situ.…”
Section: Discussionmentioning
confidence: 99%